RECONSTRUCTION OF THE QUR'AN-BASED ISLAMIC EDUCATION CURRICULUM: ESTABLISHING AL-'ADL AS A METHODOLOGICAL ETHIC AND TAQWA AS THE EVALUATION BENCHMARK - Hadiyanto; Ripan Maulana; Ghifar Ramadhan; Gangan Sayid Mikdad; Hafid Muslih (EDUPEDIA, 2025)
Contemporary Islamic education faces a profound challenge marked by a crisis of integrity and the dichotomy of knowledge, which often produces graduates with high cognitive competence but low levels of Taqwa (piety). This study aims to reconstruct a holistic and integrated framework of the Islamic Education Curriculum (IEC) grounded in the primary source of Islamic knowledge—the Quran. Employing a Qualitative Library Research approach combined with the Thematic Interpretation Method of key Quranic verses, namely QS. Al-Baqarah (2): 30, QS. An-Nahl (16): 125, and QS. Al-Maidah (5): 8, the research identifies four essential dimensions of the IEC: objectives that integrate Ubudiyah (devotion to Allah) and Khilafah (human stewardship on earth). substance emphasizing epistemic validity and comprehensive religious understanding (Tafaqquh Fiddin). pedagogical methods based on Justice operationalized through the three pillars of Hikmah, Mauizah Hasanah, and Jidal Ahsan. and evaluation that emphasizes Tazkiyah an-Nafs (purification of the soul) as the pathway toward Taqwa. The originality of this research lies in affirming that Justice must serve as the ethical foundation guiding all educational processes, as it represents the closest path to Taqwa. Consequently, this study proposes an Integrative Islamic Education Curriculum Model that centers on the practical application of Al-Adl to cultivate learners who are intellectually grounded, ethically upright, and spiritually devoted.